Study of Thermal Conductivity of Hexamethylene Tetramine and Nitrobenzene along with NaOH Doped Paperboards and their use in Electronic and Electrical Devices as Insulator (Bangladesh Journal of Scientific and Industrial Research, 2007)
Thermal conductivity of hexamethyelne tetramine and nitrobenzene along with NaOH doped papers were prepared from Bangladesh jute and their thermal properties were studied by Lee's disc method. The thermal conductivity (K) of paper boards containing HMTA along with 16 % NaOH decrease with the concentration of HMTA up to 0.3 % and then increase with the concentration of the compounds. The highest value of K=3.028x10-4 cal.cm-1sec-1 degree-1C concentration for 0.5 % HMTAand the lowest value of K=2.5x10-4cal.cm-1 sec-1 degree-1C concentration for 0.3 % HMTA but the addition of NB contents show the reverse phenomenon. Bangladesh J. Sci. Ind. Res. 41(1-2), 55-62, 2006